Construction of NiCo2O4 nanosheets-covered Ti3C2Tx MXene heterostructure for remarkable electromagnetic microwave absorption. (30th June 2022) - Zeng, Xiaojun; Zhao, Chao; Yin, Yichao; Nie, Tianli; Xie, Nuohua; Yu, Ronghai; Stucky, Galen D.
Abstract: The development of a high-performance electromagnetic microwave (EMW) absorber is pivotal for the practical realization of EMW pollution issues. However, the design of EMW absorbers with ultra-high reflection loss ( R L < −70 dB) at ultrathin matching thickness (<2 mm) still faces daunting challenges. Herein, a NiCo2 O4 nanosheets-covered Ti3 C2 Tx MXene (NiCo2 O4 NSs-MXene) heterostructure with multi-layered MXene and vertically grown ultrathin NiCo2 O4 nanosheets prepared by detachment process, reflux reaction, and heat-treatment is introduced as a new EMW absorber; this heterostructure enables a shocking EMW absorption performance with R L value of −72.3 dB at a thickness of 1.7 mm. The effective absorption bandwidth (EAB, R L < −10 dB) can also reach a relatively impressive 3.6 GHz. Furthermore, the NiCo2 O4 NSs-MXene heterostructure shows large dielectric loss derived from conductive loss, interface polarization, and dipolar polarization. The high magnetic loss in the heterostructure originates from natural resonance and eddy current loss. Hence, the synergistic effect of dielectric loss, magnetic loss, and impedance matching promote the superior EMW absorption performance of NiCo2 O4 NSs-MXene heterostructure. This achievement paves the way for the exploitation of heterostructure as an ultrathin and super-strong EMW absorption performance. Graphical abstract: Image 1